Effects of Oil Prices and Exchange Rates Movements on JSE Stock Return Volatility - Molele, Sehludi Brian; Ncanywa, Thobeka (Journal of Reviews on Global Economics, 2019)
South Africa has targeted the oil and gas sector for investment through the industrial action plan as a special economic zone. This paper focussed on the effects of oil prices and exchange rate movements in the oil and gas stock returns using the GARCH - GED model to incorporate volatility. Additionally, the paper estimates causality effects through the pairwise Granger causality techniques using secondary monthly data for the period 2007 - 2015. The findings where that change in oil prices had a positive and significant mean effect on oil and gas sector stock returns. Furthermore, changes in exchange rates had a negative and significant mean effect on the sector returns. Volatility clustering was found to be present in the sector stock returns, but volatilities associated with each of the significant variables do not last for long before it fades away. It is highly recommended that market players or investors and portfolio managers should have a keen interest on the exchange rate. While policy makers and regulators should strive to have stable exchange rate movements to offset unexpected or sudden decline of the exchange rate, depreciation. This has the detriment of additional costs through oil prices purchase by companies in the sector.